Comparison of feed-grade antibiotics in starter diets containing spray-dried blood products - Owen, K.Q.; Dritz, Steven S.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 240 pigs (initially 11.6 lb and 19 d of age) was used to compare four different feed-grade antibiotics or antibiotic combinations in phase I (d 0 to 14 postweaning) and phase II (d 14 to 28 postweaning) starter pig diets. Apramycin and carbadox were compared in the phase I diet. Combinations of tylosin/sulfamethazine and neomycin sulfate/oxytetracycline were compared in the phase II diet. No differences occurred in pig performance for the phase I and phase II periods between the feed-grade antibiotics compared in this growth assay. Therefore, determination of appropriate feed-grade antibiotic inclusion will depend on 1) economics, 2) disease profile of the herd, and 3) growth response within a particular producer's herd.
Keywords: Swine; Starter; Performance; Antibiotic